Kajian Seni Retorika dalam Pemikiran Filsafat Aristoteles: Studi Kasus Pelatihan Kader Da’i pada UKM LDM UIN Sunan Gunung Djati Bandung - Muhammad Luthfi Jalaludin Al-Habibi (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the art of rhetoric training for students. This study used a qualitative approach through literature and field studies using interview techniques. Aristotle's rhetorical theory becomes the formal object of this study. While rhetorical training is the material object. The scope and context of this research is the Unit “Kegiatan Mahasiswa” (UKM) “Lembaga Dakwah Mahasiswa” (LDM) “Universitas Islam Negeri” (UIN) Sunan Gunung Djati Bandung. The results of the research and discussion show that the art of rhetoric in Aristotle's philosophical thought is the ability to find tools of persuasion, namely the speaker's personal character, placing the audience into a certain frame of mind, and proof that comes from the content of the speech. In this regard, the training of student Da'i cadres has attempted to develop tools of persuasion, namely: 1) Student Da'i cadres are trained to have the character of militancy as a sacrifice for Islamic da'wah; 2) Da'wah narratives are not only centered on journalistic segmentation, but are developed into creator content so that it is easily accepted in the minds of today's society; and 3) Da'i cadre students are directed to hold fast to the Al-Qur'an and As-Sunnah so that their attitudes and behavior become uswah as a reflection of an Islamic campus. This study concludes that Aristotle's art of rhetoric in finding means of persuasion has been tried to be developed in the cadre of student preachers at UKM LDM UIN Sunan Gunung Djati Bandung.